Penerapan Pendidikan Multikultural di SMP Nahdlatuth Thalabah (Yasinat) Kesilir Wuluhan Jember - Winda Hurotul ‘Aini (Fakultas Ekonomi Universitas Pendidikan Ganesha, 2022)
Education is a process of human development in knowing oneself, others, and the environment. The importance of multicultural education is one of the goals in providing attitudes and thoughts to students that every human being has different abilities, so that tolerance arises based on SARA. Multicultural education is education that prioritizes the process of mutual respect for diversity and mutual respect for fellow human beings. The application of multicultural education in the school environment, because the Nahlatuth Thalabah Middle School environment has diverse backgrounds. The purpose of multicultural education is to unite the different diversity of each student. This research method is descriptive qualitative. In determining the data source is done purposively. SMP Nahdlatuth Thalabah applies multicultural education as described in the mission of SMP, namely providing worship activities as a habit and instilling a sense of ukhuwah Islamiyyah and wathoniyyah. The meaning of ukhuwah Islamiyah and wathoniyah is a sense of brotherhood based on fellow Muslims and fellow human beings. Unite a sense of brotherhood from the diversity of students who are different by respecting each other and respecting each other.